An optimized thermal cracking approach for onsite upgrading of bitumen. (1st January 2022) - Salehzadeh, Marziyeh; Kaminski, Thomas; Husein, Maen M.
Graphical abstract: Highlights: One-step non-catalytic onsite thermal cracking upgraded Alberta bitumen to pipeline API gravity and viscosity. Assessment of peptization value (P-value) suggested unstable product. Upgraded asphaltenes showed higher aromaticity, shorter alkyl side chains and lower H/C ratio. Quenching of the upgraded oil did not impact asphaltenes stability. Viscosity and API gravity of the upgraded oil did not depreciate much even after 12 days. Abstract: Onsite partial upgrading is a promising strategy for facilitating pipeline transportation of bitumen without the use of diluent. In the present work, a one-step treatment using an autoclave is optimized toward upgrading Alberta bitumen of 9.6 API gravity and 925, 000 cP viscosity. The thermal cracking process was kept simple in order to maintain an economic and environmental advantage. Optimum conditions entailed 75 min of reaction time at 420 °C, without quenching the reactor. These conditions corresponded to highest centrifuged oil product yield of 73.3 ± 1.1 wt%, viscosity of 34 ± 2 cP and API gravity of 18.9 ± 0.5. H-NMR, CHNS and FTIR measurements revealed thermally cracked asphaltenes having more aromatic parts with shorter aliphatic side chains. Subsequently, the P-value of the thermally cracked product was much lower (1.11) than the bitumen feed (3.9) and was not impacted by quenching. Nevertheless, the degradation of viscosity and API gravity of the oil product and its centrifuged cut were less than 5% after 12 days.